Validation of the Measurement Model of the Grief Support Healthcare Scale Among the Intensive Care Unit Nurses in Malaysia - Gurbinder Kaur, Jit Singh; Low, Wah Yun; Khatijah Lim, Abdullah * (Istanbul University-Cerrahpasa University Press, 2022)
Aim: This study aimed to establish the validity and reliability of the measurement model of the Grief Support Healthcare Scale sub-constructs among the intensive care unit (ICU) nurses.